Donor Impurity in CdS/ZnS Spherical Quantum Dots under Applied Electric and Magnetic Fields - Kobra Hasanirokh; Adrian Radu; Carlos A. Duque (Nanomaterials, 2022)
This article presents a theoretical study of the electronic, impurity-related, and nonlinear optical properties of CdS/ZnS quantum dots subjected to electric and magnetic fields. The magnetic field is applied along the z-axis, with the donor impurity always located in the center of the quantum dot. In the case of the electric field, two situations have been considered: applied along the z-axis and applied in the radial direction (central electric field). In both cases, the azimuthal symmetry (around the z-axis) is preserved. In the absence of a magnetic field and considering a central electric field, the system preserves its spherical symmetry both in the presence and in the absence of the donor impurity. The study is carried out in the effective mass approximation and it uses the finite element method to find the eigenfunctions and their corresponding energies, both in the presence and in the absence of the impurity. This work investigates the optical absorption coefficient and the relative change of the refractive index, considering only intraband transitions between l = 0 states (states with azimuthal symmetry concerning the z-axis). Calculations are for z-polarized incident radiation. The study shows that the combined effects of a central electric field and a z-directed magnetic field can give rise to a typical core/shell-like quantum confinement with oscillations of the electron ground state. Additionally, it is shown that the presence of the donor impurity suppresses such oscillations and it is responsible for blue shifts in the optical properties and magnifications of the corresponding resonances.